2017
DOI: 10.3892/ol.2017.6614
|View full text |Cite
|
Sign up to set email alerts
|

High expression of MAGE-A9 is associated with unfavorable survival in esophageal squamous cell carcinoma

Abstract: Melanoma-associated antigens (MAGEs) are a group of well-characterized members of the cancer/testis antigen family, which are expressed in a variety of malignant tumors. MAGE-A9, a subfamily of MAGE-As, has been studied in a number of types of cancer and have been associated with unfavorable survival outcome. However, the expression of MAGE-A9 in human esophageal squamous cell carcinoma (ESCC) and association of MAGE-A9 with the clinicopathological characteristics of ESCC, particularly prognostic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated an association between the prognosis of ESCC patients and expression of several members of the melanoma-associated antigen (MAGE) gene family, including MAGE-A9 (7), MAGE-A11 (8), and MAGE-D4 (9). Another member of this family, preferentially expressed antigen of melanoma (PRAME), has been reported to play a role in the progression of various malignant tumors, including head and neck squamous cell carcinoma (10)(11)(12)(13)(14).…”
Section: Abstract Background/aim: To Investigate the Function Of Pref...mentioning
confidence: 99%
“…Previous studies have demonstrated an association between the prognosis of ESCC patients and expression of several members of the melanoma-associated antigen (MAGE) gene family, including MAGE-A9 (7), MAGE-A11 (8), and MAGE-D4 (9). Another member of this family, preferentially expressed antigen of melanoma (PRAME), has been reported to play a role in the progression of various malignant tumors, including head and neck squamous cell carcinoma (10)(11)(12)(13)(14).…”
Section: Abstract Background/aim: To Investigate the Function Of Pref...mentioning
confidence: 99%
“…Epidemiological evidence has indicated that the prognosis of patients with early-stage ESCC is good; however, this sharply declines upon the progression of the disease to an advanced stage. The recurrence and metastasis of ESCC is the pivotal factor leading to the death of patients with advanced disease ( 4 ). To date, multiple factors have been reported to be involved in the progression to the advanced stage of ESCC ( 5 , 6 ); however, the underlying mechanisms remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Another study on Chinese ESCC patients revealed that there was a significant MAGE-A9 up regulation in ESCC tissues compared with normal. Moreover, the levels of MAGE-A9 expression was significantly correlated with grade, size, and lymph node involvement [123].…”
Section: Main Textmentioning
confidence: 99%